2020
DOI: 10.31688/abmu.2020.55.3.05
|View full text |Cite
|
Sign up to set email alerts
|

"COVID-19 prevention and control: a study of the knowledge, awareness and attitude towards the disease among radiology departments staff in Sudan"

Abstract: La stratégie d'adaptation en tant que moyen de prévenir l'épuisement émotionnel chez les médecins de soins primaires : un essai contrôlé randomisé Introduction. L'épuisement professionnel est l'un des principaux problèmes non résolus des professionnels de la santé. Compte tenu de la situation récente de l'infection au COVID-19 et du stress psychologique associé, ce problème devient extrêmement critique dans le monde. Objectif. L'étude visait à valider l'efficacité de la stratégie d'adaptation d'Asimov auprès d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
4
3
0
Order By: Relevance
“…Where NGOs provided a high percentage of training on hand hygiene and PPE use, the government should expand its educational and training programs for employees. This is similar to the findings of a study, in Sudan, where 65% of MIWs reported that they had training on hand hygiene, and 75% of them had knowledge about hand hygiene (Elgyoum et al, 2020).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Where NGOs provided a high percentage of training on hand hygiene and PPE use, the government should expand its educational and training programs for employees. This is similar to the findings of a study, in Sudan, where 65% of MIWs reported that they had training on hand hygiene, and 75% of them had knowledge about hand hygiene (Elgyoum et al, 2020).…”
Section: Resultssupporting
confidence: 89%
“…them. This is similar to study held in Sudan among radiology staff were 90% of respondents reported that the disinfectant should be used after contact with every suspected/confirmed COVID-19 patients (Elgyoum et al, 2020). While in a study among HCWs in radiology departments in Saudi Arabia, there were 67.2% of participants have knowledge about the types of disinfectants and how to prepare them (Aljondi et al, 2020).…”
Section: Resultssupporting
confidence: 77%
“…Repeatedly throughout the literature, a theme that uncertainty causes stress and clarity leads to confidence, in other words, knowledge is power is demonstrated clearly. 7e11, 34,36,42,44 With emerging clarity on the process for infection, a trend of reported increase in knowledge and compliance with these infection control procedures are being observed 28,34,36 due to appropriate communication within healthcare units including the radiography departments.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, radiographers observed that their own work-related stress was transferred to their family, partners, and friends. 7,8,14,40,42,44,46,48 Some redeployed radiographers also reported being stressed due to the need to adjust to new working environments and technologies. 7,75,77 Anxiety from these stressors was a commonly reported theme.…”
Section: Theme 3: Workforce Mental Health and Well-beingmentioning
confidence: 99%
See 1 more Smart Citation